(untitled) (Research, Society and Development, 2021)
Objective: To present a concept of dental vulnerability based on the opinion of oral health professionals in Brazil. Methods: A cross-sectional study performed in two stages: preparation of a questionnaire by literature search and its application with oral health specialists. The data were analyzed by means of Bardin technique and descriptive analysis. Results: A total of 188 professionals from all regions of Brazil responded to the questionnaire. The answers were classified into seven dimensions, conceptualizing dental vulnerability as a set of social, structural, overall health, mental, and oral health factors, in addition to factors involving the health services and public management that influence the health-disease process dynamic. Conclusion: The concept of dental vulnerability produced from the opinions of the professionals from different regions of Brazil allows advancement to new studies on the theme and the development of instruments aiming to measure the phenomenon.